2003
DOI: 10.1116/1.1593647
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and structure of ultrathin yttrium oxide films for Si field effect transistor gate dielectric applications

Abstract: Photoemission and ab initio theoretical study of interface and film formation during epitaxial growth and annealing of praseodymium oxide on Si(001) Soft x-ray photoelectron spectroscopy using synchrotron radiation has been employed to study the interface between Y 2 O 3 films and Si͑100͒. Y 2 O 3 films of ϳ8, ϳ15, and 65 Å were formed by plasma assisted chemical vapor deposition on HF-last Si͑100͒. With this deposition technique, SiO 2 forms at the interface and a kinetically limited silicate layer forms betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Y 3d photoelectron spectra were interpreted considering both NIST data and previously reported results. Analysis of core-level Y 3d high-resolution spectra (Y 3d 3/2 and Y 3d 5/2 spin–orbit components) in the 154–164 eV region showed that a reliable difference in binding energy values for the Cl-LYH and B-LYH samples is observed (see Figure S8, Supporting Information). Y 3d core levels for closo -dodecaborate intercalated layered yttrium hydroxide shifted (ca.…”
Section: Results and Discussionmentioning
confidence: 98%
“…Y 3d photoelectron spectra were interpreted considering both NIST data and previously reported results. Analysis of core-level Y 3d high-resolution spectra (Y 3d 3/2 and Y 3d 5/2 spin–orbit components) in the 154–164 eV region showed that a reliable difference in binding energy values for the Cl-LYH and B-LYH samples is observed (see Figure S8, Supporting Information). Y 3d core levels for closo -dodecaborate intercalated layered yttrium hydroxide shifted (ca.…”
Section: Results and Discussionmentioning
confidence: 98%
“…Before sputtering, the O 1s peak shows three components at BE positions of 529.0 eV (assigned to Y-O bonds), 531.6 eV (assigned to Y-OH bonds) and 533.5 eV (assigned to adsorbed water species). [28][29][30] The existence of Y-OH bonds and adsorbed water species is in accordance to the ALD process, which ended with a water pulse and purge and thus, reactive hydroxyls can remain on the surface (Fig. 3a).…”
mentioning
confidence: 92%
“…A weak signal is also visible at around 153 eV, associated to the Si 2s peak of adsorbed silicon species (2.6 at% of Si was detected on the as-introduced sample), probably originating from adsorption of silicon grease during transfer of the sample to the spectrometer. 28,29,31 The C 1s peak reveals three different contributions at 284.7 eV (carbon, C-H, major), 285.9 eV (C-OH, minor) and 289.2 eV (O-C]O, minor) as depicted in Fig. S5, † attributed to adventitious carbon (the carbon amount in the sample as-introduced was 35.4 at%).…”
mentioning
confidence: 99%
“…Sometimes the shift of the Y 3d peak towards higher BE is attributed to an increased incorporation of OH-groups into the Y 2 O 3 film. 26,49 In our case, a stoichiometry of O:Y ¼ 1.43 for the as deposited films and O:Y ¼ 1.55 for the annealed Y 2 O 3 are measured (on Si) which means that also a strengthen build-in of OH groups during annealing can partly contribute to the observed peak shift. Almost no signal from sub-stoichiometric GeO x can be detected within our detection limit, and also for the annealed samples there is no evidence given for a metallic YGe phase with a reported shift in BE of $0.9 eV towards lower binding energies compared to the Ge 0 state.…”
Section: B Xps Analysismentioning
confidence: 98%